2006
DOI: 10.5694/j.1326-5377.2006.tb00203.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between hospital overcrowding and mortality among patients admitted via Western Australian emergency departments

Abstract: Objective: To examine the relationship between hospital and emergency department (ED) occupancy, as indicators of hospital overcrowding, and mortality after emergency admission. Design: Retrospective analysis of 62 495 probabilistically linked emergency hospital admissions and death records. Setting: Three tertiary metropolitan hospitals between July 2000 and June 2003. Participants: All patients 18 years or older whose first ED attendance resulted in hospital admission during the study period. Main outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
224
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 672 publications
(236 citation statements)
references
References 18 publications
7
224
4
1
Order By: Relevance
“…In the current study, the average daily hospital occupancy was 92.3% and the average arrival density index was 7.6—both figures are highly consistent with the findings by Forster et al 18. In a study of Australian inpatients, a clear linear relationship was demonstrated between an overcrowding hazard scale score of greater than 2 and inpatient mortality, even after adjusting for age, diagnosis, referral source, urgency and mode of transport to the hospital 14. On average, the overcrowding hazard scale in the current study did not exceed 2.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, the average daily hospital occupancy was 92.3% and the average arrival density index was 7.6—both figures are highly consistent with the findings by Forster et al 18. In a study of Australian inpatients, a clear linear relationship was demonstrated between an overcrowding hazard scale score of greater than 2 and inpatient mortality, even after adjusting for age, diagnosis, referral source, urgency and mode of transport to the hospital 14. On average, the overcrowding hazard scale in the current study did not exceed 2.…”
Section: Discussionsupporting
confidence: 91%
“…The first was the “overcrowding hazard scale”, which tests the combined effects of hospital and ED crowding. The possible scores range from 1 to 9, with the higher score indicating greater crowding 14. The second was the “arrival density index”, designed to measure how busy the ED was when a patient arrived (ie, number of patients who arrived in the ED in the preceding hour for every patient).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, three studies have looked at mortality associated with crowding. Two papers from Australia have shown increased mortality in patients admitted from overcrowded departments,34 76 although the definition used in one of these papers is a little hazy. Two papers I found,77 78 along with two reported by Pham et al ,67 failed to find an association between ambulance diversion and increased mortality, although the results may be confounded by system factors (even during diversion many centres will still receive critically ill patients).…”
Section: Effects Of Crowdingmentioning
confidence: 99%
“…It has been suggested that most self-referrals can be treated by the GP,1 but exact numbers and research on this topic are missing. This so-called inappropriate use of EDs should be reduced as much as possible, because it results in ‘overcrowding’, longer waiting times, more diagnostic tests and higher costs 6 7…”
Section: Introductionmentioning
confidence: 99%